Evaluation on Habaring Hurung Pier Pontoon to Improve Service in East Kotawaringin Transport System, Central Kalimantan Province - Nur Fareha Binti Mohamad Zukri; Kodrat Alam; M.Noor Rizki Hidayat (IWJ : Inland Waterways Journal, 2019)
East Kotawaringin has a relatively large area, namely 16.796 km2 or 10.94 percent of the area of ​​Central Kalimantan province. With an area of ​​regional the East Kotawaringin divided into 17 districts, mostly lowlands. Kotawaringin East region which thousands of cities in Sampit City astronomically lies between 112⁰ 7 '29 "East until 113⁰ 14' 22" East and 1⁰ 11'50 "south latitude to 3⁰ 18 '51" South Latitude. Geographically, in the western part bordering Seruyan District, the north to east by Katingan, and directly adjacent to the southern part of the Java Sea. This district has a topography that varies between 3-85 meters above sea level.The pier is one of the parts that are used to perform an activity arrival and departure of ships, up and down the passenger and cargo handling. The role of the pier is very important to support these activities. To support these activities, the pier used must be in good condition so that the activities coming and departing ships, up and down the passenger and unloading can proceed smoothly. But Pier of Habaring Hurung infrastructure conditions in East Kotawaringin need attention, especially from the manager in this case is the Department of Transportation Kotawaringin East Central Kalimantan province as conditions dock floor height fixed type that does not correspond to the freeboard boat at low tide and condition-type floating dock made of wood and many parts have been weathered, the absence of mooring facilities, bridges poorly and docks are flooded due to the tilt of the wooden pier so that the activity of ships berthing and unloading at the docks less safe, smooth and comfortable for service users, Based on the analysis carried out that the need for evaluation and the addition of facilities and planning of facilities to improve existing services at Pier Habaring Hurung.